Mere saṃvāda : sākshātkāra - Kardama, Jayaprakāśa (Aman Prakashan, 2013)
Compilation of interviews of Jayaprakāśa Kardama, born 1958, Hindi author, on his life, works, dalits, and Hindi literature on dalits.